Characterization of Activated Carbon from Granulated Sugar - Muhammad, Muhammad; Mulyawan, Mulyawan; Rahman, M R F; Suryati, Suryati (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
Activated carbon that potentially acts as an adsorbent was prepared from granulated sugar. The activated sugar was prepared through a dehydration process followed by a chemical activation process with a concentrated NaOH solution. To comprehend the properties of prepared ready carbon, characterization of the carbon was needed to be conducted. The conducted methods for prepared activated carbon were FTIR for detecting present functional groups attached to carbon, BET to identify the porous structure of synthesized carbon, SEM method as a morphological indicating method on synthesized carbon, and carbon thermal stability characteristic information from the TGA method. It was found that the prepared activated carbon contained various functional groups. The distinguished functional groups presented were carboxylic acid, free alcohol, NH2, and SO3. The readily activated carbon showed a rough surface to enhance the adsorption process on the synthesized carbon from the SEM characterization method. BET on the readily activated carbon revealed that the activated carbon exhibited type IV isotherm, consisting dominantly of mesopores and micropores as a minority. TGA characterization method showed that the thermal stability of carbon was significantly unstable in the range of 100â„ƒ and around 200â„ƒ. It implies that the prepared activated carbon contained OH as one of its functional groups. With all the characterization methods conducted on the readily activated carbon from granulated sugar, it was found that the prepared carbon had the potential to be utilized as an adsorbent. Moreover, it is suggested that the granular sugar-based carbon should be investigated in the following future study in the wastewater treatment process.